Taxation and entrepreneurship in the United States - Hans A. Holter; Serhiy Stepanchuk; Yicheng Wang (University of Oslo, Department of Economics, 2023)
This paper studies the effects of income taxation on entrepreneurship, empirically and in a structural macro model with entrepreneurial choice. Combining state-level tax data with household and firm data we document that higher and more progressive taxation has a strong negative impact on entrepreneurial activity across time and space. A one percentage point increase in the tax rate at median income leads to 4.5% fewer entrepreneurs and 1.5% fewer employees at small firms, whereas a 1% increase in the progressivity of the tax schedule leads to 1.0% fewer entrepreneurs and 0.2% fewer employees at small firms. To explain this relationship and to evaluate the impact of taxation on output and welfare, we develop a life-cycle, incomplete markets model of the labor market with entrepreneurial choice. The model generates elasticities of entrepreneurship to taxation that are similar to those found in the empirical analysis. Progressive taxation lowers both the risk and return to becoming an entrepreneur. However, quantitatively the return effect dominates. We find that converting to a flat tax (while keeping the level of taxes constant) would increase the number of entrepreneurs by 25% and output by 4.5%. Under the assumption of a small open economy, the level of tax progressivity that maximizes steady state welfare is, however, only slightly lower than for the current U.S. tax code. Allowing for general equilibrium effects, the socially optimal tax code is about half as progressive as today and would lead to a 0.4% welfare gain if implemented.
Keywords: E20; E62; H24; J24; J48; L26; 330; Entrepreneurship; Taxation; Tax Progressivity; Business Risk; Insurance